2019
DOI: 10.2147/ott.s191157
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpression of shugoshin1 predicts a poor prognosis for prostate cancer and promotes metastasis by affecting epithelial&ndash;mesenchymal transition</p>

Abstract: The aim of the study was to investigate the role of shugoshinl (SGO1) in human prostate cancer (PCa). Materials and methods: Quantitative real-time PCR (qRT-PCR) was used to determine the expression of SGO1 in PCa tissues and cell lines. The correlation between SGO1 expression and clinicopathological characteristics of PCa patients was analyzed using Kaplan-Meier analysis. SGO1 siRNA was successfully constructed and transfected into PCa cell lines (LNCaP and PC3). The knockdown efficacy was assessed by qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…For instance, SGOL1, a member of the shugoshin family of proteins, is thought to protect centromeric cohesion during mitosis, and its dysregulation at centromeres can lead to chromosome missegregation and miotic arrest [40, 41]. Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42]. In addition, SGOL1 has been found in other cancers (e.g., breast cancer and glioblastoma) [4345].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SGOL1, a member of the shugoshin family of proteins, is thought to protect centromeric cohesion during mitosis, and its dysregulation at centromeres can lead to chromosome missegregation and miotic arrest [40, 41]. Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42]. In addition, SGOL1 has been found in other cancers (e.g., breast cancer and glioblastoma) [4345].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, forkhead transcription factor (FoxM1) functions as an oncogene in the initiation, development, and progression of cancer, and its neoplastic functions can be used as a strong biomarker for the diagnosis and treatment of cancer (21). In prostate cancer, numerous prognostic biomarkers were also investigated (22)(23)(24). For instance, minichromosome maintenance 10 replication initiation factor (MCM10) was revealed to be significantly upregulated in prostate cancer patients, and overexpression of MCM10 promoted cell proliferation and predicted poor prognosis in prostate cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…29,3133 Other authors have also shown a role for Sgo1 in tumorigenesis and EMT. 15,34 However, no study has linked Sgo1 to EMT in TNBC.…”
Section: Introductionmentioning
confidence: 99%